PERAN MAHASISWA PLP II DALAM MEMBANTU PROSES PEMBELAJARAN AKTIF DI LINGKUNGAN SEKOLAH SMKN 1 BONE - Rijaluddin, Khalid; Fatimah Arif, Nur; Yuliani; Musfirawati; Muh. Haerul Ikshan, Andi; Dzalsabila , Zhafira; Fadliansyah, Muhammad; Amelia , Eka; Muskamal Irba , Muh.; Faizal; Khairul; Cha Ashari, Cha; Yusril, Muhammad; Rahmat , Waidin; Fatahillah , Ikhwanul; Rinaldi; Hasan , Zafar; Ardiansyah , Andi; Anugrah , Rian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School Field Introduction Program (PLP) 2 is one of the programs aimed at providing real experience for students in the learning process at schools, which is also one of the compulsory courses. This article aims to describe the role of PLP II students in assisting the active learning process at SMKN 1 Bone. The method used in this study is a qualitative descriptive method with observation, documentation, and direct experience techniques during the implementation of PLP II. The results of the study show that PLP II students play an important role in assisting teachers during the learning process, increasing student participation through discussions and question- and-answer activities, as well as supporting various school activities. The presence of PLP II students provides a positive contribution to the learning environment and helps create a more active and interactive learning process at school.